An unusual pedigree with microcornea-cataract syndrome. Issue 10 (October 1995) - Stefaniak, E; Zaremba, J; Cieślińska, I; Kropińska, E
Abstract : A pedigree with 14 patients affected with microcornea-cataract (MC) syndrome is described. MC syndrome is very rare and this pedigree is probably the sixth to be reported. Transmission is most likely autosomal dominant, but the unusual feature of the present family is the fact that the proportion of affected members is so high that one is tempted to suspect preferential transmission of the chromosome carrying the MC gene.